EXPLORING THE IMPORTANCE OF REFERENCING IN HIGHER EDUCATION IN UZBEKISTAN: A COMPREHENSIVE ANALYSIS OF ACADEMIC EXCELLENCE - Djurayeva , Nargiza Kudratillayevna (Educational Research in Universal Sciences, 2023)
The article takes a deep dive into the significance of referencing within the context of higher education in Uzbekistan. It thoroughly examines the various referencing styles employed by higher education institutions in Uzbekistan and provides valuable insights into why referencing holds a crucial position in achieving academic excellence. By upholding academic integrity and elevating research quality, referencing offers a multitude of advantages that greatly influence a student’s educational path. Moreover, the article serves as a guide for students and scholars on the proper citation of sources, offering practical tips and recommending citation management tools to ensure accuracy and adherence to referencing styles. It highlights the fundamental skill of proper citation, not only as a means to prevent plagiarism but also as a way to enhance the credibility and professionalism of academic papers.